Hematopoietic Stem/Progenitor Cell Dependent Participation of Innate Lymphoid Cells in Low-Intensity Sterile Inflammation - Korniotis, Sarantis; Thornley, Thomas B.; Kyriazis, Periklis; Theodorou, Evangelos; Ma, Lingzhi; Li, Lisa S.; Kokkotou, Efi; Strom, Terry B.; Koulmanda, Maria (Frontiers in Immunology, 2018)
Hematopoietic stem/progenitor cells (HSPC) are characterized by their unique capacities of self-renewal and multi-differentiation potential. This second property makes them able to adapt their differentiation profile depending on the local environment they reach. Taking advantage of an animal model of peritonitis, induced by injection of the TLR-2 ligand, zymosan, we sought to study the relationship between bone marrow-derived hematopoietic stem/progenitor cells (BM-HSPCs) and innate lymphoid cells (ILCs) regarding their emergence and differentiation at the site of inflammation. Our results demonstrate that the strength of the inflammatory signals affects the capacity of BM-derived HSPCs to migrate and give rise in situ to ILCs. Both low- and high-dose of zymosan injections trigger the appearance of mature ILCs in the peritoneal cavity where the inflammation occurs. Herein, we show that only in low-dose injected mice, the recovered ILCs are dependent on an in situ differentiation of BM-derived HSPCs and/or ILC2 precursors (ILC2P) wherein high-dose, the stronger inflammatory environment seems to be able to induce the emergence of ILCs independently of BM-derived HSPCs. We suggest that a relationship between HSPCs and ILCs seems to be affected by the strength of the inflammatory stimuli opening new perspectives in the manipulation of these early hematopoietic cells.